The Effect of Using Short Animation Movie on Listening Comprehension Ability of 8th Grade Students at SMPN 2 Pematangsiantar - Kristiani, Theresa Nanda; Manalu, David Berthony; Purba, Rudiarman (Innovative: Journal Of Social Science Research, 2025)
The goal of this research is to ascertain to implement of using short animation movie method on listening comprehension of students grade eight The objective of this research is to find out whether there is significant effect of using short animation movie method on listening comprehension of grade eight students of SMP Negeri 2 Pematangsiantar. This research was quantitative research in the form of experimental design. The data obtained in the form of data on student test scores. In the experimental class, the pre-test scores ranged from a minimum value of 2 to a maximum value of 44, with a mean score of 19.32 and a standard deviation of 11.545. Following the intervention, the post-test scores ranged from a minimum value of 24 to a maximum value of 78, with an average (mean) score of 51.03 and a standard deviation of 13.205. This significant improvement highlights the effectiveness of using short animation movies in enhancing students' listening comprehension skills. Conversely, the control class exhibited pre-test scores ranging from a minimum value of 4 to a maximum value of 40, with a mean score of 21.03 and a standard deviation of 9.061. The post-test scores for this group ranged from a minimum value of 20 to a maximum value of 92, with an average (mean) score of 58.84 and a standard deviation of 14.531. While the control class also showed improvement, the progress was less pronounced compared to the experimental class, underscoring the advantages of implementing short animation movies as a teaching tool. Overall, the findings support the conclusion that utilizing short animation movies significantly enhances listening comprehension ability among students. The results indicate that this engaging and interactive approach effectively promotes listening skill development, highlighting the importance of innovative teaching methods in educational practices.